Incidência da sindrome pré-menstrual na prática de esportes - David, Alexandra Martins [UNIFESP] (2009)
Despite the increasing number of women who practice physical exercise, there are still few reports concerned with anatomy, psychology and mainly hormones that could affect their performance. Although there is a multitude of articles about the effects of physical exercise in menstruation, only a few of them report how this function interferes in women's performance. The association physical exercise - menstruation has been studied but without considering the changes during the cycle, the perimenstrual symptoms. Therefore, the aim of this article was to investigate the incidence and periodicity of pre-menstrual symptoms in athletes. A daily questionnaire was applied with the aim to follow the pre-menstrual symptoms during a period of 3 consecutive months. The population of the study was composed by 31 female athletes in fertile age. RESULTS: The prevalence of PMS in athletes was of 71% and the mainly reported symptoms were irritability (86.5%), mood swings (77.3%) and cramps (72.7%). Other symptoms were reported by 59% of the athletes during the pre-menstrual period. CONCLUSION: Our data show a high prevalence of PMS among athletes.